Streptococcus oralis Employs Multiple Mechanisms of Salivary Mucin Binding That Differ Between Strains - Chahal, Gurdeep; Quintana-Hayashi, Macarena P.; Gaytán, Meztlli O.; Benktander, John; Padra, Medea; King, Samantha J.; Linden, Sara K. (Frontiers in Cellular and Infection Microbiology, 2022)
Streptococcus oralis is an oral commensal and opportunistic pathogen that can enter the bloodstream and cause bacteremia and infective endocarditis. Here, we investigated the mechanisms of S. oralis binding to oral mucins using clinical isolates, isogenic mutants and glycoconjugates. S. oralis bound to both MUC5B and MUC7, with a higher level of binding to MUC7. Mass spectrometry identified 128 glycans on MUC5B, MUC7 and the salivary agglutinin (SAG). MUC7/SAG contained a higher relative abundance of Lewis type structures, including Lewis b/y, sialyl-Lewis a/x and α2,3-linked sialic acid, compared to MUC5B. S. oralis subsp. oralis binding to MUC5B and MUC7/SAG was inhibited by Lewis b and Lacto-N-tetraose glycoconjugates. In addition, S. oralis binding to MUC7/SAG was inhibited by sialyl Lewis x. Binding was not inhibited by Lacto-N-fucopentaose, H type 2 and Lewis x conjugates. These data suggest that three distinct carbohydrate binding specificities are involved in S. oralis subsp. oralis binding to oral mucins and that the mechanisms of binding MUC5B and MUC7 differ. Efficient binding of S. oralis subsp. oralis to MUC5B and MUC7 required the gene encoding sortase A, suggesting that the adhesin(s) are LPXTG-containing surface protein(s). Further investigation demonstrated that one of these adhesins is the sialic acid binding protein AsaA.